Equivalence tuning of Strike Limit Algorithms - H. Givens, Geof; Punt, Andree; A.O. BERNSTEIN, TIFFANY (J. Cetacean Res. Manage., 1999)
Equivalence tuning involves adjusting a candidate aboriginal whaling management Srrike Limit Algorithm (SLA) to enable fair comparison with respect to its ability to satisfy the objectives for aboriginal subsistence whaling. Two methods for equivalence tuning ('depletion tuning' and 'H-tuning') are reviewed and compared. Conceptually, H-tuning is appealing because it accounts for aboriginal subsistence need as well as risk explicitly, whereas depletion tuning is based only on risk. However, H-tuning is only approximate, whereas depletion tuning is exact. Whale dynamics are slow so the choice among alternative SLAs is likely to be one related to a simple catch/risk trade-off. Hence, it is reasonable to favour the simpler depletion tuning approach if it can be implemented in a manner that facilitates fair and reasonable comparison. However, in one example shown, H-tuning was more successful at finding a comparison level that reflected an appropriate catch/risk balance.